THE EFFECT OF RECEIVABLES TURNOVER AND INVENTORY TURNOVER ON PROFITABILITY IN AUTOMOTIVE AND COMPONENT COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2010-2019 PERIOD - Oktavia, Senny; Suparno, Suparno (Jurnal Ekonomi Balance, 2020)
This study aims to determine the effect of account receivable turnover and inventory turnover on profitability (ROA). The population in this study are automotive companies and components listed on the indonesia Stock Exchange Period 2010 - 2019.The sampling method used was purposive sampling and obtained 4 companies as samples. The research method used a quantitative approach and data analysis using multiple linear regression analysis, classical assumption test, descriptive statistical analysis, determination analysis and hypothesis testing. Based on the results of multiple linear regression tests show that account receivable turnover and inventory turnover together (simultaneously) has a positive and significant effect on profitability (ROA), because tcount > ttable (5,052 > 3,252), and a significant value of 0,011 < 0,05. Partially, receivable turnover has a negative but significant effect on profitability (ROA), because tcount < ttable (-3,141 < 2,026), and significant value of 0,003 < 0,05. Inventory turnover has a positive and significant effect on profitability(ROA), because tcount > ttable (2,488 > 2,026), and significant value of 0,017 < 0,05.